Granulomatous inflammation in ginbuna crucian carp Carassius auratus langsdorfii against Mycobacterium gordonae - Goshi, Kato; Taichi, Kakazu; Mitsuo, Yamada; Lau, Lik Ming; Kazue, Nakajima; Shoh, Sato; Teruyuki, Nakanishi; Makoto, Endo; Motohiko, Sano (Elsevier B.V., 2019)
In this study, we investigated the immune responses against Mycobacterium gordonae in ginbuna crucian carp. Cumulative mortality of ginbuna injected with 2.0 × 10^7 CFU of M. gordonae was 50% at 170 days post-infection. CD4-1, CD8α, T-bet and IFNγ2 gene expression levels were significantly upregulated in ginbuna injected with 1.9 × 10^8 CFU of M. gordonae at 21 and 28 days post-infection. The CD4-2 level did not change during the experiment. Granulomatous responses consisted of central macrophage accumulation and surrounding lymphocytes, and Ziehl-Neelsen-positive bacteria were observed in the trunk kidney of the challenged fish. Immunohistochemistry using anti-ginbuna IFNγs and anti-ginbuna CD4-1 polyclonal antibody revealed that the marginal lymphocytes were positive for CD4-1, and the IFNγ-producing cells surrounded the mycobacterial cell-laden phagocytes. These results suggest that CD4-1+ cells and IFNγ2 play important roles in the granulomatous inflammation against Mycobacterial infections in teleosts.